ICA Based EOG Artifact Identification and Removal from EEG Signal: Preprocessing Using SASICA - Ms. A.Vidhya and Dr.R.Parameswari, (International Journal of Advanced Science and Technology, 2020)
EEG (Electro Encephalogram) is the most common technique used for the diagnosing the seizure, it captures the electrical signals produced by the brain. For diagnosing the Epilepsy, EEG signals are captured from the patients by placing the electrodes on the scalp. Epilepsy is a persistent non communicable ailment of the brain that influences around 50 millions human worldwide. It is characterized with the aid of recurrent seizures, which are short episodes of involuntary motion  that may additionally contain a section of the  partial or the generalized and are on occasion  occasion accompanied by using loss of focus and manage of bowel or bladder function. While recording the EEG signals many artifacts are present like movement of eyes, eye lid movement and eye ball movements are Electrooculogram (EOG), muscle movement and sweating are Electromyogram (EMG) and cardiac movements (ECG). This paper analyzed the techniques to remove the Ocular artifacts(EOG) present in the EEG using MATLAB EEGLAB plug-in.